Soviet Russia/the USSR and transformation of the international relations system in the first half of the 1920s - E. V. Romanova (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The paper examines the formation of the Soviet state and its place within the European international relations system in the first half of the 1920s both in the context of new principles of interstate interaction, the character of economic relations between countries, and geopolitical transformations triggered by the First World War. The first section covers the political and ideological aspects of relations between Soviet Russia/the USSR and Western countries. The author shows that, despite the prominence of ideological conflict in the development of the IR system that emerged after the First World War, continuous tensions both between the defeated and the victors and among the latter urged the political and military elites of Western states to consider the Soviet Russia as a situational partner even under the Bolsheviks rule. The difference in the assessments of the ideological conflict with Soviet Russia, and then with the USSR by Western statesmen stemmed from the difference in their assessments of the prospects for the evolution of the Soviet regime, as well as of the commitment of the Soviet leaders to the idea of the world revolution. The second section of the paper focuses on the role that was assigned to the Soviet state in various plans for the European economy reconstruction after the First World War. While the largest European states, Great Britain and Germany in particular, were interested in involving the Soviet state in the system of trade and economic relations (to get access to its resources in order to restore their own economies, and to open up the prospect of transforming the Soviet system towards capitalism), the Soviet leaders considered access to the European market as a necessary condition for the industrialization which was seen as the key to survival of the first socialist state in a hostile capitalist environment. In this regard the author notes that although Soviet Russia advocated for the revolutionary transformation of the entire IR system, she was unable to enforce it and eventually turned into a status quo power. However, the awareness of hostility by the Western world and the desire to preserve its unique socio-economic order, kept Moscow from attempts to integrate deeply into the Versailles system. In turn, the Western leaders, for all the differences in their approaches towards the Eastern European region and despite de facto recognition of the USSR demonstrated the growing alienation towards the Soviet regime as they became disillusioned with the prospects for its possible transition. This inability to predict the future development of the USSR, as well as to control the situation in Eastern Europe in general were among the factors that instigated the leading European power — Great Britain — to devise a scheme of the European security system without the USSR, which was embodied in the Locarno agreements of 1925.